Studying the effect of impurities Bi2O3 to SiO2 used in LCD screens - Wlla M. Mohammed (Tikrit Journal of Pure Science, 2019)
In this study, a liquid crystal display LCD cell was prepared. with the windows made from a thin film of SnO2 add to it Bi2O3 by weight (0,1,3,5,7)% .The effect of adding optical and electrical properties of the cell was studied. The thin film was prepared by vacuum evaporation technique. It was added to use powder mixing technique. The results showed a decrease in the value of the current passing through the cell and  an increase in resistance value from 9.7MΩ to 12.5MΩ. The results also showed an increase in the cell's ability to control the light and darkness it with lower voltages by increasing the add rate. This leads to a decrease power used of a single cell. The value of the capacitance is not affected by the addition of Bi2O3 and  was stable at ( 3nf ±1% ).